Techno-economic optimization of level and raise spacing in Bushveld Complex platinum reef conventional breast mining. - Musingwini, C. (The Southern African Institute of Mining and Metallurgy., 2010)
The Bushveld Complex is economically significant and strategically important to South Africa, thus it is imperative that optimal extraction of platinum group metal (PGM) resources on the Bushveld Complex is achieved. Optimal extraction broadly requires that the maximum amount of ore is extracted by excavating and hauling the minimum amount of waste in the shortest possible time, at the least cost, and in the safest and most environmentally acceptable manner. In open-pit mine planning this entails among other things, minimizing the waste stripping ratio, whereas in underground mine planning it includes minimizing the metres of waste development In conventional mining, the main development that is in waste or partly in waste and defines the mining grid pattern, includes levels and raises. It was prudent to consider optimizing level and raise spacing in conventional mining because the method is a prevalent mining method on the Bushveld Complex accounting for nearly 70% of platinum production. The techno-economic optimization of level and raise spacing is characteristically a multi-criteria decision analysis (MCDA) optimization process and should therefore be analysed using MCDA techniques. The analytic hierarchy process (AHP) was the most appropriate MCDA technique for this research study. By using an orebody code named OB1 based on real geological data that was typical of Bushveld Complex platinum reef deposits, the derived optimal range of vertical level spacing was 30 m-50 m, and the optimal range of raise spacing was 180 m-220 m. The research methodology used in this study and the results obtained were received positively by the South African platinum mining Industry because for the first time in several decades, a holistic methodology and practically acceptable solution had been developed for the controversial debate of optimizing level and raise spacing for conventional mining.
Transaction paper.
Keywords: Techno-economic optimization; Multi-criteria decision analysis (MCDA); Concentrated mining; Lagrange multiplier; Analytic hierarchy process (AHP); Valuation curve; Backlength; Open pit mining; Platinum